2005
DOI: 10.1210/en.2004-0935
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Stimulates Protein Synthesis and Inhibits Proliferation in Primary Cultures of Rat Adrenal Glomerulosa Cells

Abstract: Angiotensin II (Ang II) is one of the most important stimuli of rat adrenal glomerulosa cells. The aim of the present study was to investigate whether Ang II can stimulate cell proliferation and/or hypertrophy and investigate pathways and intracellular targets. A 3-d treatment with Ang II (5-100 nm), through the Ang II type 1 receptor subtype, abolished cell proliferation observed in control cells but increased protein synthesis. Preincubation with PD98059 (a MAPK kinase inhibitor) abolished basal proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 62 publications
3
48
0
1
Order By: Relevance
“…In line with this provocative hypothesis, activation of ERK1/2 resulted in a growth arrest of PC12 cells and induced neuronal differentiation in that cellular system . Also in rat adrenal zona glomerulosa cells ERK1/2 activation blocked cell proliferation and stimulated steroidogenesis (Otis et al 2005, Otis & Gallo-Payet 2007. A role of ERK1/2 for functional aspects of cortical ( Wu et al 2002, Chang et al 2008 or medullary cells (Cox & Parsons 1997, Takekoshi et al 2001, Shibuya et al 2002, Yanagihara et al 2005, Shinkai et al 2007) has also been provided by others.…”
Section: Intracellular Control Of Adrenal Growthmentioning
confidence: 85%
See 2 more Smart Citations
“…In line with this provocative hypothesis, activation of ERK1/2 resulted in a growth arrest of PC12 cells and induced neuronal differentiation in that cellular system . Also in rat adrenal zona glomerulosa cells ERK1/2 activation blocked cell proliferation and stimulated steroidogenesis (Otis et al 2005, Otis & Gallo-Payet 2007. A role of ERK1/2 for functional aspects of cortical ( Wu et al 2002, Chang et al 2008 or medullary cells (Cox & Parsons 1997, Takekoshi et al 2001, Shibuya et al 2002, Yanagihara et al 2005, Shinkai et al 2007) has also been provided by others.…”
Section: Intracellular Control Of Adrenal Growthmentioning
confidence: 85%
“…For the human adrenocortical carcinoma cell line H295R it has been suggested that angiotensin II stimulated mitogenesis might occur via ERK1/2 activation ( Watanabe et al 1996). By contrast, in non-malignant rat adrenal glomerulosa cells, angiotensin II mediated induction of ERK1/2 phosphorylation resulted in an inhibition of cell proliferation (Otis et al 2005). Since in the same system angiotensin II stimulated hypertrophy, protein synthesis and steroidogenesis via a mechanism involving both ERK1/2 and p38 MAPK, the effects on growth seem to be related to functional aspects of zona glomerulosa cells (Otis & Gallo-Payet 2006).…”
Section: Effectors Of Erk1/2 Activation In Adrenocortical Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…A first screen of these cells using a protein kinase array for signal transduction protein expression and phosphorylation (Figure 4) indicated the involvement of mitogen-activated protein kinases (MAPK) such as ERK1/2. In addition, it has been shown recently that in cultured rat glomerulosa cells, AngII increases protein synthesis including the expression of the steroidogenic enzymes and steroidogenic acute regulatory protein (StAR) via the p42/p44 MAPK and p38 MAPK pathways, 20 and the stimulation of hormone secretion in aldosterone-producing glomerulosa cells. 21 Therefore, the role of ERK1/2 MAPKs in fat cell-induced aldosterone secretion was determined in human H295R adrenocortical cells and isolated human adrenocortical cells in primary culture.…”
Section: Introductionmentioning
confidence: 99%
“…2,9 This MAPK activation after stimulation of the (P)RR with renin occurs relatively late, with a maximum described after 30 min, 2 compared with ang II stimulation experiments that peak at about 5 min. 10 In addition, Akt kinase, which itself is located downstream of PI3K, can activate MAP kinases by mechanisms involving, for example, protein kinase C and nitric oxide 11,12 (Figure 2). Therefore, we speculate that PLZF acts upstream of MAP kinases (Figure 2), which is supported by a recent publication that reports that expression of PLZF can enhance the activity of ERK kinase.…”
Section: Signal Transduction Of the (P)rrmentioning
confidence: 99%